Latilactobacillus curvatus DCF0620 and postbiotics derived from soybean germ reduce colitis severity by modulating fibrosis and gut dysbiosis - Park, Jin-Sil; Kang, Hye Yeon; Choi, JeongWon; Lee, Wonjong; Seong, Hyunbin; Cho, Sang Hee; Lee, Su Beom; Han, Nam Soo; Choi, Jaekwon; Lee, Bo-In; Cho, Mi-La (Frontiers in Immunology, 2026)
BackgroundGiven that microbiota dysbiosis is closely linked to the initiation and progression of inflammatory bowel disease (IBD), extensive research is underway to utilize beneficial probiotics as a therapeutic strategy for IBD. In this study, we compared the therapeutic efficacy of Lacticaseibacillus paracasei (L. paracasei) DCF0420, Lactiplantibacillus plantarum (L. plantarum) DCF0514, and Latilactobacillus curvatus (L. curvatus) DCF0620 and also investigated the potential of soybean germ-based postbiotics from DCF0620 as a treatment for IBD.MethodsLive L. paracasei DCF0420, L. plantarum DCF0514, L. curvatus DCF0620, or postbiotics were orally administered to DSS-induced colitis mice starting 7 days before DSS injection until the end of the experiment. Weight changes and the disease activity index were evaluated to assess disease severity. Inflammation and fibrosis were analyzed pathologically in intestinal tissue. Fecal samples from mice injected with postbiotics were subjected to 16S rRNA gene sequencing. Cytokine levels in spleen cell culture supernatants were measured by ELISA, and fibronectin levels in CCD-18Co cells were analyzed by Western blot.ResultsTreatment with L. paracasei DCF0420, L. plantarum DCF0514, or L. curvatus DCF0620 increased the production of IL-10 in murine splenocytes in a dose-dependent manner under stimulation with anti-CD3 antibody or LPS. Furthermore, administration of each probiotic strain reduced the levels of fibronectin induced by TGF-β in CCD-18Co cells. In the DSS-induced colitis murine model, administration of L. curvatus DCF0620 effectively attenuated disease severity. Mechanistically, L. curvatus DCF0620 treatment controlled the infiltration of cells that express pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-17) and fibrotic markers (TGF-β, Col1, and α-SMA) into the intestinal tissue of DSS-induced colitis mice. Notably, administration of soybean germ-based postbiotics derived from L. curvatus DCF0620 also demonstrated therapeutic efficacy in the DSS-induced colitis mice, specifically by improving the dysbiosis observed in the colitis mice.ConclusionOur findings suggest that L. curvatus DCF0620 and its soybean germ-based postbiotics represent promising therapeutic agents for IBD by demonstrating potent anti-inflammatory, anti-fibrotic, and gut microbiota-modulating effects.